Solitary Pyogenic Liver Abscesses - Gateño, Nisso; Lucinschi, Alicia; Yametti, Luis (Cirugía del Uruguay, 1979)
Study of solitary pyo·genic abscesses of the l'iver based on analysis of a series of 9 cases. This condition has a low incidence rate, clinical diagnosis- is difficult and it is necessary to determine the number and topography of supurative foci. Elective treatment is surgery and correct bacterio'logical testing of pus is essential for determining postoperatory antibiotic theraphy.